Diagnosis And Therapy Of Escherichiosis Of Lambs In Uzbekistan (Texas Journal of Agriculture and Biological Sciences, 2024)
The article presents studies of infection from the first days of life of lambs and the course of the disease. Clinical signs, pathoanatomical autopsy are presented. Changes in lymph nodes and parenchymal organs, growth and development during bacteriological studies. Serogroup strains have been isolated.